Functional Empowerment of Psychological Skills for Guidance and Counseling Teachers - Nuryati, Atamimi (Fakultas Psikologi UGM, 2010)
Education is an important indicator to measure the progress of a nation. Guidance and Counseling (GC) teachers have an important role in improving the quality of the students as an indicator of the quality of teaching and learning activities. BK PROAKTIF model of psychological skill training is designed with the aim to help improve the function of GC teachers in particular and GC institution into an environment that is effective, efficient, safe, and comfortable for students in particular and related circles in general (parents, fellow teachers, school personnels). This research method is designed in four stages, namely: survey, experimental activities, monitoring and research data analysis. As independent variables: BK PROAKTIF model of psychological skills training; as dependent variable: the perception of self, perception of the profession as a GC teacher, self-esteem, self-confidence, job satisfaction and work motivation are selected based on the need assessment in research and theoretical concepts that stresses on the role of the six variables in the individual self-improvement